Statistical processing of very small random circle samples - Шенгур, Светлана Виталиевна (Technology audit and production reserves, 2014)
This article represents the statistical analysis of the very small random circle samples. The main purpose of the paper is to develop and experimentally investigate the new technique of statistical processing of circular data, received from various sources and spheres of activity. The bootstrapping is chosen as the basis method. The developed technique allows obtaining sample circular mean direction and its confidence interval. The usage of the proposed technique allows improving the accuracy of the confidence interval for the mean direction in comparison with traditional method. The research results can be applied for further investigations in scientific researches or used as independent development in such areas as metrology, biotechnology, medicine, economics, aviation, radiolocation etc.